(untitled) (Journal of Information Technologies in Education (ITE), 2011)
The most popular Internet services and the methodical guidelines for their use in distance learning are considered in the article. The experience in usage Internet services in distance learning courses developed in the distance learning system “Kherson Virtual University” is examined.